The correlation between communication skill and basic teaching skill of prospective biology teachers - Arwita, Widya; Hasruddin, Hasruddin; Ningsih, Widia; Mukra, Rizal; Mira Rangkuti, Sailana; Bella Junniar, Amanda (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to determine the correlation between communication skills and basic teaching skills of biology education students as prospective biology teachers at the State University of Medan. The method used in this study is a quantitative approach with correlational data analysis, with a sample of 30 students. Data collection using observation techniques. Data analysis in the form of linearity tests and Pearson product-moment correlation tests. Data on communication skills and basic teaching skills are normally distributed and have a linear correlation. However, after the correlation test was carried out, the significance. (2-tailed) The value was obtained between communication skills and basic teaching skills of 0.063> 0.05, which means that there is no significant correlation between communication skills and basic teaching skills. Meanwhile, based on the calculated r (Pearson Correlation) of 0.344, the strength of the correlation is that there is a low correlation between communication skills and basic teaching skills. So it can be concluded that communication skills and basic teaching skills have a low correlation.